On the Role of Illness Duration and Nutrient Restriction in Cholestatic Alterations that Occur During Critical Illness. Issue 2 (August 2018) - Jenniskens, Marc; Güiza, Fabian; Oorts, Marlies; Vander Perre, Sarah; Derde, Sarah; Dufour, Thomas; Thiessen, Steven; Annaert, Pieter; Van den Berghe, Greet; Langouche, Lies
ABSTRACT: Background and Aims: Elevated markers of cholestasis are common in response to critical illness, and associated with adverse outcome. The role of illness duration and of nutrient restriction on underlying molecular pathways of such cholestatic responses have not been thoroughly investigated. Methods: In a mouse model of surgery- and sepsis-induced critical illness, molecular pathways of cholestasis were investigated up to 7 days. To assess which changes are explained by illness-induced lack of feeding, nutrient-restricted healthy mice were studied and compared with ad libitum fed healthy mice. Furthermore, serum bile acid (BA) concentrations were quantified in 1, 114 human patients with either short or long intensive care unit (ICU) stay, matched for type and severity of illness, up to ICU-day-7. Results: In critically ill mice, either evoked by surgery or sepsis, circulating and hepatic BA-levels progressively increased with time from day-3 onward, preceded by unsuppressed or upregulated CYP7A1 and CYP27A1 protein expression. From 30 h onward, nuclear farnesoid-X-receptor-retinoid-X-receptor staining was significantly suppressed in both critically ill groups, followed from day-3 onward by decreased gene expression of the apical exporter BA-specific export pump and increased expression of basolateral exporters multidrug resistance-associated protein 3 (MRP3) and MRP4. Nutrient restriction in healthy mice only partly mirrored illness-induced alterations in circulating BA and BA-transporters, without changing nuclear receptors or synthesis markers expression. Also in human critically ill patients, serum BA increased with time in long-stay patients only, similarly for patients with or without sepsis. Conclusions: Circulating BA concentrations rose days after onset of sepsis- and surgery-induced, critical illness, only partially explained by lack of feeding, preceded by suppressed nuclear feedback-sensors and ongoing BA synthesis. Expression of transporters suggested ongoing reversed BA-flow toward the blood. Abstract : Supplemental Digital Content is available in the text